2005
DOI: 10.1016/j.adolescence.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: A longitudinal investigation of the relation between a negative cognitive triad and depressive symptoms in youth

Abstract: The present study examined self‐reported depressive symptoms and associated cognitive features by reporting data from a 1‐year longitudinal study of a community sample of 93 children and 69 adolescents. Results revealed that in childhood a negative cognitive triad appeared to be more a consequence than a predictor of depressive symptoms after 1 year. In adolescence, a negative view of the future was predictive of depressive symptoms after 1 year. A negative cognitive triad also appeared to be a consequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…Orth, Robins, and Roberts (2008) found low self-esteem prospectively predicted subsequent depression, but depression did not predict subsequent levels of self-esteem. In contrast, Timbremont and Braet (2006) showed that a negative self-view appeared to be more a consequence than a predictor of depressive symptoms after 1 year in childhood. There may be important age-related factors involved (Demo 1992) as adults' negative self-evaluation were not associated with change in depressive symptoms over time (Shahar and Davidson 2003), and otherwise showed weaker effects than those of adolescents (McGrath and Repetti 2002).…”
Section: Directional and Third Variable Explanations Of Co-occurring mentioning
confidence: 71%
See 1 more Smart Citation
“…Orth, Robins, and Roberts (2008) found low self-esteem prospectively predicted subsequent depression, but depression did not predict subsequent levels of self-esteem. In contrast, Timbremont and Braet (2006) showed that a negative self-view appeared to be more a consequence than a predictor of depressive symptoms after 1 year in childhood. There may be important age-related factors involved (Demo 1992) as adults' negative self-evaluation were not associated with change in depressive symptoms over time (Shahar and Davidson 2003), and otherwise showed weaker effects than those of adolescents (McGrath and Repetti 2002).…”
Section: Directional and Third Variable Explanations Of Co-occurring mentioning
confidence: 71%
“…For instance, harsh discipline uniquely predicted boys' internalizing problems and girls' externalizing problems, whereas maternal depression uniquely predicted increases in boys' externalizing problems and girls' internalizing problems (Leve et al 2005). Negative self-concept, the focus of this study, is shown to be a risk factor for internalizing and externalizing problems for both boys and girls, and yet strength of the relationships between self-concept and problem behaviors varies across gender (Timbremont and Braet 2006;Ybrandt 2008). It is interesting to note that in problem behaviors with unequal gender ratios, the group with the lower prevalence often is more seriously affected-a phenomenon in the literature described as gender paradox (Loeber and Keenan 1994;Vierhaus and Lohaus 2008).…”
Section: Sex Differencesmentioning
confidence: 88%
“…Extant research regarding self-schemas and depressive symptoms among youth has focused almost exclusively on the role of negative self-schemas. This research suggests that negative self-schemas are associated with increased risk and maintenance of depressive symptoms among children and adolescents (Abela and Sullivan 2003;Calvete et al 2015;Carter and Garber 2011;Garber et al 1993;Hammen and Zupan 1984;Hankin et al 2004;Kercher et al 2009;Lewinsohn et al 2001;Lumley and Harkness 2007;Timbremont and Braet 2006). For example, Garber et al (1993) found negative self-schemas were associated with depressive symptoms in a sample of approximately 700 adolescents.…”
Section: Self-schemas and Child And Adolescent Depressionmentioning
confidence: 84%
“…Cognitive distortions, as well as other cognitive vulnerability factors, have been shown to precede and maintain different forms of psychopathology (Beck 1967; Beck et al 1985). Cognitive errors (e.g., overgeneralization, catastrophizing, selective abstraction) and the cognitive triad (i.e., negative views of self, world, and future) are two types of cognitive distortions that have been associated with depression in youth (Jacobs et al 2008; Timbremont and Braet 2006). There is also evidence to suggest that cognitive errors are associated with anxiety among adolescents (Weems et al 2001).…”
Section: Introductionmentioning
confidence: 99%